Social attitudes toward inclusion: Recent research advances - Omote, Sadao [UNESP] (FapUNIFESP (SciELO), 2018)
The Salamanca Declaration, signed in 1994, promoted discussions on a new proposal, the inclusion, and so the focus of attention moved from the person with disability to his/her environment. Such change contributed to give more attention to the social approaches in the studies of disabilities. Although the study of disabilities as a social phenomenon has had its highlight in the middle of the last century in the international scenario, only a half century later Brazilian researches began to be influenced by social thoughts. The presence of social thoughts in the discussions about inclusion influenced the nature of research in the area. This text analyzes the progress that happened in the studies of the social attitudes toward inclusion. In a brief historical description, some scales of social attitudes available for research with both adults and children are presented. The existence of reliable instruments of data collection contributed to broaden the research on social attitudes toward inclusion. The most important results suggest that social attitudes toward inclusion can be modified through activities programmed for this purpose. Thus, a school environment can be built with genuinely supportive social attitudes throughout the school environment.
Atitudes sociais em relação à inclusão: Recentes avanços em pesquisa
Keywords: Educational inclusion; Social attitudes; Special Education